Epidemiological Profile of Asymptomatic Bacteriuria in Pregnant Women at the Mother and Child University Hospital Center of N’Djamena: Associated Risk Factors and Antibiotic Resistance (London Journal of Research In Science: Natural and Formal, 2024)
Asymptomatic bacteriuria in pregnant women is a bacterial urinary tract infection without any of the typical symptoms that are associated with a urinary tract infection whose urine culture meets the criteria for urinary tract infection corresponding to a colony count greater than 100 x 10 6 forming units of bacteria per liter. The objective of this work was to determine the prevalence of asymptomatic bacteriuria in pregnant women and to evaluate the effectiveness of antibiotics against isolated bacteria to better care for pregnant women. This is a prospective and analytical study based on the cytobacteriological  xamination of urine including 185 pregnant women who came to the prenatal consultation service of the University Hospital for Mother and Child, from January 2022 to December 2022. The isolation, identification and sensitivity tests of the isolated bacteria to antibiotics were carried out under standard clinical microbiology conditions.Among 185 pregnant women who were screened by urine cytobacteriological examination, 91 (49.18%) cases were positive. The average age of the patients was 27.08 years with extremes ranging from 16 to39 years. The age group of 22 to 27 years old was predominant with a rate of 35.16% followed by that of 28 to 33 years old (31.87%). The bacterial strains isolated were Escherichia coli (37.63%), Streptococcus agalactiae (23.65%), Klebsiella pneumoniae (4.30%), Mycoplasma hominis (4.30%), Ureaplasma spp (3.22%) and Pseudomonas aeruginosa (2.15%). The antecedents most frequently associated with asymptomatic bacteriuria were urinary infections (43.96%) followed by 13.19% cesarean section.The antibiogram of bacterial agents showed an average resistance of 47.43% of Escherichia coli to beta-lactams. 100% of Staphylococcus aureus were sensitive to fusidic acid and 90.91% resistant to vancomycin. Ureaplasma spp and Mycoplasma homonis developed an average resistance of 50% to fluoroquinolones and 25% to (lincosamides, macrolides and tetracycline). This study not only revealed the high level and frequency of bacteria associated with urinary infections in pregnant women, but also showed a strong resistance of bacteria and especially Escherichia coli to aminopenicillins and a high sensitivity of Staphylococcus aureus to acid. fusidic.
Keywords: MHD; Free convective; Inclination; Poiseuille flow; Runge-Kutta method.; Climate Change; social crisis; collapse; Asymptomatic bacteriuria; pregnant woman; antibiotic resistance; risk factor